Digging down into the global urban past. (August 2021) - Hart, Emma; Dantas, Mariana
Abstract: In our introduction to this Special Issue on early modern cities and globalization, we explore the current place of cities before 1850 in global urban history and address the promise of a greater focus on their role. We argue that the interplay between the large scale and the small scale in the imperial global city is an essential dialogical force in the formation of each city's relationship to the wider early modern world. Furthermore, early modern global urban history can help explain the creation of spaces that facilitated connections between distant, global locations, as well as illuminate the emergence of networks of exchange between city communities around the globe. Yet, it also reveals the tense, messy negotiation of the meaning of these urban spaces, as well as the incredibly diverse communities they harboured.